Exploring the synergy between mechanical and radiation shielding properties in Ni–Ti–Hf shape memory alloys - Khattari, Z Y (Bulletin of materials science, 2025)
This study investigates γ-ray shielding properties of Ni–Ti–Hf shape memory alloys under uniaxial tension, correlating their mechanical properties with linear attenuation coefficients (LAC). We evaluated LAC (cm –1 ) values across various photon energies ( E (MeV)), Ti:Hf ratio and APF, revealing an increase in LAC as ( E , Ti:Hf, APF, LAC): (0.1, 2:3, 0.70, 32.5) to (0.1, 0:5, 0.74, 49.8) for samples subject to maximum deformation. The mechanical properties were also found to correlate very well with the γ-rays attenuation under optimal conditions. Notably, the plastic deformation of the alloys was found to enhance radiation shielding performance, with a significant reduction in γ-ray transmission (e.g., LAC = 1520 cm –1 ) observed in samples with higher mass recovery (e.g., 120%) rates post-deformation. These findings underscore the importance of maintaining alloy density and optimizing mechanical properties for effective radiation shielding in practical applications.